Akuntansi Dan Sistem Informasi Dengan Kompetensi Di Bidang Teknologi Informasi - Dedi Karmana; Mira Ismirani Fudsy; Sakti Muda Nasution; Zen Munawar (LPPM POLITEKNIK LP3I BANDUNG, 2024)
This research aims at the need for Accounting and Information Systems to be supported by an information technology basis. To implement Accounting and Information Systems on a technology basis, a user group is needed that focuses on how to learn how to implement accounting and information systems based on information technology. As well as what methods and alternatives can make its implementation easier. Specifically, researchers need to know what and how the challenges of using appropriate methodology in implementing Information Technology-based Accounting and Information Systems are in their implementation. This research is limited by providing a brief and easy to understand description of research methods, application of the method and challenges in using the method. Having literacy in the form of quotes from previous research that has applied this method will give researchers a good basic tool for evaluating the usefulness of the method. This research includes examples of several challenges that researchers will face as well as possible strategies that can be used so that the realization of the research objectives can be achieved. It is hoped that the results of the research will provide the best method that can show how technology-based accounting and information systems can be applied.